2011
DOI: 10.1080/08870440903411039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of illness representations dimensions and illness representation clusters in predicting outcomes in the first year following diagnosis of type 2 diabetes: Results from the DESMOND trial

Abstract: This article explores the utility of cluster analysis of illness representations, in comparison to analysing each dimension of the individual's illness representation, to predict an individual's response to diagnosis of type 2 diabetes. Participants in a large multi-centre randomised controlled trial of a self-management education intervention for people with type 2 diabetes, completed measures of illness beliefs (coherence, timeline, impact, seriousness, personal responsibility) and depression along with HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
1
36
2
1
Order By: Relevance
“…More specifically illness perceptions relating to diabetes consequences are associated with poorer emotional wellbeing (Hudson, Bundy, Coventry & Dickens 2014), and personal control mediates the relationship between diabetes distress and HbA1c (Gonzalez, Shreck, Psaros & Safren 2015). Clustering individuals with Type 2 diabetes according to shared illness perception schemas is also shown to provide a useful predictor of depression overtime (Skinner et al 2011); however it is not yet known whether shared illness perception schemas predict diabetes distress.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically illness perceptions relating to diabetes consequences are associated with poorer emotional wellbeing (Hudson, Bundy, Coventry & Dickens 2014), and personal control mediates the relationship between diabetes distress and HbA1c (Gonzalez, Shreck, Psaros & Safren 2015). Clustering individuals with Type 2 diabetes according to shared illness perception schemas is also shown to provide a useful predictor of depression overtime (Skinner et al 2011); however it is not yet known whether shared illness perception schemas predict diabetes distress.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries the peak incidence for type 2 diabetes is noted in adults aged about 65 years (Wild, Roglic, Green, Sicree, & King, 2004). Thus, patients significantly younger may perceive the disease as more burdensome and stigmatizing (Skinner et al, 2011), and insulin therapy as interfering with their occupational career (Reach et al, 2013) or social life, which would contribute to increasing NA. As compared to the "no response" subgroup, patients from the ambivalent subgroup representing "challenge response" rated their material status lower and more often had vocational education.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both valences were assumed to be mutually independent, thus separate analyses of change were conducted for negative and positive affect and then their interrelationships were assessed. Finally, since the existing research suggests that sociodemographic variables can differentiate both the affective functioning (Gallo & Matthews, 2003), and potentially also adaptation to illness (Skinner et al, 2011), an attempt was made in our study to examine whether the membership in a specific patient subgroup, defined by trajectories of positive and negative affect changes, would be significantly related to sociodemographic characteristics. Therefore, the following research questions were posed: 1.…”
mentioning
confidence: 99%
“…The processes may impact illness representations as well. Skinner and colleagues (2011) found that depression, as measured by a depression screener (HANDS; Zigmond et al, as cited in Skinner et al, 2011) was associated with CSM "cluster" membership. That is, depressed individuals were more likely to belong to a resisters accepting consequences cluster or a resisters cluster of CSM beliefs than more positive CSM clusters.…”
Section: Psychosocial Factors and The Self-regulation Modelmentioning
confidence: 99%
“…Research has supported the IPQ-R as having acceptable to excellent reliability 2011), and it has been used to measure change in illness perceptions in previous diabetes research trials (Davies et al, 2008;Skinner et al, 2011).…”
Section: Illness Representationmentioning
confidence: 99%